The mushroom hunt - Frazer, Simon; Dale, Penny (Cambridge, Mass. : Candlewick Press, 1995)
Combines stories, poems, and artwork with facts and ideas to help children learn about mushrooms.
School Library Journal.
Booklist.
Appraisal-Science Books for Young People.
4.7
K-3
Keywords: Mushrooms -- Juvenile literature; Mushrooms; Mushrooms; Mushrooms